Elementary School Social Studies Learning Problems During the Implementation of the Independent Curriculum - Anggraini, Cicilia Clara Devi (Widyagogik, 2023)
The purpose of this study is to describe in more depth the problems that exist in the aspects of teacher readiness, availability of resources, as well as evaluation and monitoring of social studies learning in the independent curriculum. This kind of inquiry is called a literature study. Books, articles or scientific papers, theses, dissertations, encyclopedias, and other pertinent sources are some examples of the literature that was used. This study demonstrates This study found several problems with social studies learning in the independent curriculum in the aspects of teacher readiness, resource availability, as well as evaluation and monitoring. Efforts that can be made are providing training for teachers in implementing the curriculum, using and even developing resources, and conducting evaluations. This effort requires support from the government and other educational communities.